2023
DOI: 10.3389/fpls.2023.1275399
|View full text |Cite
|
Sign up to set email alerts
|

Plant long non-coding RNAs: identification and analysis to unveil their physiological functions

Edmundo Domínguez-Rosas,
Miguel Ángel Hernández-Oñate,
Selene-Lizbeth Fernandez-Valverde
et al.

Abstract: Eukaryotic genomes encode thousands of RNA molecules; however, only a minimal fraction is translated into proteins. Among the non-coding elements, long non-coding RNAs (lncRNAs) play important roles in diverse biological processes. LncRNAs are associated mainly with the regulation of the expression of the genome; nonetheless, their study has just scratched the surface. This is somewhat due to the lack of widespread conservation at the sequence level, in addition to their relatively low and highly tissue-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 149 publications
(147 reference statements)
0
2
0
Order By: Relevance
“…Regulatory ncRNAs, on the other hand, are divided into two classes based on their length: long-non-coding RNAs (lncRNAs) exceeding 200 nucleotides and small non-coding RNAs (sRNAs), including microRNAs (miRNAs) of 19-25 nucleotides, small interfering RNAs (siRNAs) of 20-24 nucleotides, and piwi-interacting RNAs (piRNAs) with a length of 24-32 nucleotides [10,11]. The ncRNAs are further categorized based on chromosomal location, sequence/structure, ways of splicing, and biological functions [12,13]. Recently, a unique group of endogenous ncRNAs called "circular" RNAs (circRNAs) with a closedloop structure has been identified [14,15].…”
Section: Small Interfering Rnas (Sirnas)mentioning
confidence: 99%
“…Regulatory ncRNAs, on the other hand, are divided into two classes based on their length: long-non-coding RNAs (lncRNAs) exceeding 200 nucleotides and small non-coding RNAs (sRNAs), including microRNAs (miRNAs) of 19-25 nucleotides, small interfering RNAs (siRNAs) of 20-24 nucleotides, and piwi-interacting RNAs (piRNAs) with a length of 24-32 nucleotides [10,11]. The ncRNAs are further categorized based on chromosomal location, sequence/structure, ways of splicing, and biological functions [12,13]. Recently, a unique group of endogenous ncRNAs called "circular" RNAs (circRNAs) with a closedloop structure has been identified [14,15].…”
Section: Small Interfering Rnas (Sirnas)mentioning
confidence: 99%
“…These RNAs are mostly transcribed in the nucleus with RNA polymerase II in an mRNA-like way. The mechanisms by which plant lncRNAs function are numerous, and some of them are better understood in animals [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Recent studies have shown that the short open reading frames (sORFs) of some plant lncRNAs encode functional small peptides (micropeptides) with a size of around 5 to 100 amino acids [ 10 , 12 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%